2005
DOI: 10.1074/jbc.m412521200
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of the Scorpion Toxin Maurocalcine into Cells

Abstract: Maurocalcine (MCa) is a 33-amino-acid residue peptide toxin isolated from the scorpion Scorpio maurus palmatus. External application of MCa to cultured myotubes is known to produce Ca 2؉ release from intracellular stores. MCa binds directly to the skeletal muscle isoform of the ryanodine receptor, an intracellular channel target of the endoplasmic reticulum, and induces long lasting channel openings in a mode of smaller conductance. Here we investigated the way MCa proceeds to cross biological membranes to rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Recent studies have shown that the scorpion toxin maurocalcine crosses the plasma membrane, reaches its target channel located in the endoplasmic reticulum, and consequently causes calcium release from intracellular stores (54). It has been suggested that maurocalcine behaves similarly to the well known cell-penetrating peptides (55), such as the human immunodeficiency virus Tat peptide (56), although recent efforts to understand the translocation mechanism of cell-penetrating peptides have revealed greater complexity involving multiple pathways (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the scorpion toxin maurocalcine crosses the plasma membrane, reaches its target channel located in the endoplasmic reticulum, and consequently causes calcium release from intracellular stores (54). It has been suggested that maurocalcine behaves similarly to the well known cell-penetrating peptides (55), such as the human immunodeficiency virus Tat peptide (56), although recent efforts to understand the translocation mechanism of cell-penetrating peptides have revealed greater complexity involving multiple pathways (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…As previously (7,9,22), through macropinocytosis (23). The cell penetration of MCa b / Strep complexes involves one or multiple steps of attachment to the membrane through binding to cell surface glycosaminoglycans and negatively charged lipids.…”
Section: Removing Disulfide Bridges In Mca Disrupts the Secondarymentioning
confidence: 99%
“…These observations suggested that MCa is able to cross the plasma membrane to reach its pharmacological target. This was first demonstrated when a biotinylated analogue of MCa was coupled to a fluorescent derivative of streptavidin, and the complex was shown to cross the plasma membrane (4). Cell penetration of this MCa-based complex is rapid, reaches saturation within minutes, and occurs at concentrations as low as 10 nM (5).…”
Section: Maurocalcine (Mca)mentioning
confidence: 99%